Perspectives on negation and polarity items - Hoeksema, Jacob, 1956- (Linguistik aktuell, 2001)
This study hypothesises that neg-raising is a cognitive phenomenon which arises while the human mind is processing the content of the sentence under the normal assumption of closed world. A 'neg-raised sentence' conveys an epistemic attitude towards the proposition expressed by the subordinate clause. The hedge consists in making it clear that a certain conclusion is compatible with the current information state, but cannot be proven